Penguatan Kapasitas Produksi dan Manajemen UMKM Pangan berbasis K3 dan Digital Marketing di Desa Suci Kecamatan Panti - Anggraeni, Oktanita Jaya; Kurniawati, Dewi; Dhamayanthi, Wenny; Ismail, Andi Muhammad; Rizky, Dian (Jurnal SOLMA, 2026)
Background: Food-based Micro, Small, and Medium Enterprises (MSMEs) in Suci Village, Panti District, hold significant potential for strengthening the rural economy but face constraints in production efficiency, business management, and occupational health and safety (OHS) practices. This community engagement program aimed to enhance technical and managerial capacity through appropriate production technology, financial literacy training, OHS implementation, and digital marketing adoption. Method: The program was conducted over three months with two partner enterprises using a participatory approach and a pre–post evaluation design. Results: Results show a 35% reduction in production time (from 4 hours to 2.6 hours per cycle), a 40% increase in daily output (30 kg to 42 kg), a 60% improvement in financial literacy scores (45 to 72), and an increase in personal protective equipment compliance from 20% to 80%. The number of regular customers also increased from 18 to 26 following the digital promotion. Conclusion: The intervention effectively fostered structured, safer, and data-informed business practices and demonstrates scalability potential for sustainable rural MSME empowerment.